Peer Group Support untuk Menurunkan Tingkat Depresi pada Lansia di UPT PSLU Blitar - Bisepta Prayogi (STIKes Patria Husada Blitar, 2016)
Indonesia has entered an era where the population structure is elderly and estimated that in 2020 the number of elderly reach 28.8 million (11.34%) peoples with a life expectancy of 71.1 years old. As people getting old, aging and physical changes are unavoidable. This changes can lead to mental disorders. Depression is one of the many common mental disorders in the elderly due to aging. Based on data in Canada, 5-10% of elderly living in the community are depressed, while those living in the institutional environment of 30-40% have depression and anxiety. One effort that can be done to deal with depression in the elderly is to use intervention Peer Group Support. Methods: This research used Pre-Experiment with the one group pre-post test design. The total sample was 30 respondents taken by purposive sampling. The data were analyzed by Paired T Test,with significance value of 0.05. Results:based on test result of the paired t test, there was differences in level of depression before and after peer group support (p=0,001). Discussion:with the provision of peer group support interventions,it could reduce the level of depression in the elderly at UPT PSLU Blitar.